Experiential Neurorehabilitation: A Neurological Therapy Based on the Enactive Paradigm - Martínez-Pernía, David (Frontiers in Psychology, 2020)
With the arrival of the cognitive paradigm during the latter half of the last century, the theoretical and scientific bases of neurorehabilitation have been linked to the knowledge developed in cognitive neuropsychology and cognitive neuroscience. Although the knowledge generated by these disciplines has made relevant contributions to neurological therapy, their theoretical premises may create limitations in therapeutic processes. The present manuscript has two main objectives: first, to explicitly set forth the theoretical bases of cognitive neurorehabilitation and critically analyze the repercussions that these premises have produced in clinical practice; and second, to propose the enactive paradigm to reinterpret perspectives on people with brain damage and their therapy (assessment and treatment). This analysis will show that 1) neurorehabilitation as a therapy underutilizes body-originated resources that aid in recovery from neurological sequelae (embrained therapy); 2) the therapeutic process is based exclusively on subpersonal explanation models (subpersonal therapy); and 3), neurorehabilitation does not take subjectivity of each person in their own recovery processes into account (anti-subjective therapy). Subsequently, and in order to attenuate or resolve the conception of embrained, sub-personal and anti-subjective therapy, I argue in support of incorporating the enactive paradigm in rehabilitation of neurological damage. It is proposed here under a new term, “experiential neurorehabilitation”. This proposal approaches neurological disease and its sequelae as alterations in dynamic interaction between the body structure and the environment in which the meaning of the experience is also altered. Therefore, when a person is not able to walk, remember the past, communicate a thought, or maintain efficient self-care, their impairments are not only a product of an alteration in a specific cerebral area or within information processing; rather, the sequelae of their condition stem from alterations in the whole living system and its dynamics with the environment. The objective of experiential neurorehabilitation is the recovery of the singular and concrete experience of the person, composed of physical and subjective life attributes.